2014
DOI: 10.3109/0886022x.2014.985995
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure of rats during prenatal period to radiation spreading from mobile phones on renal development

Abstract: Background: The aim of this study was to investigate the effects of exposure to a 900-MHz electromagnetic field (EMF) produced by mobile phones on the renal development of prenatal rats. Histopathological changes and apoptosis in the kidneys, together with levels of urea, creatinine and electrolyte in serum were determined. Methods: A total of 14 Sprague-Dawley rats were studied. Pregnant rats were divided into two equal groups: a control group and an EMF-exposed group. The study group was exposed to 900-MHz o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
8
0
5
Order By: Relevance
“…EMA grubuna ait kafeslerin ortasına 20 gün süreyle ve 24 saat boyunca 900 MHz radyo frekansı radyasyonu üreten dijital bir sinyal üreteci olan dijital modülasyon sinyal üreteci (Anritsu MG3670 B tipi, Japonya) cihazının anteni konulmuştur. [21] Dijital modülasyon sinyal üreteci cihaz, mobil iletişim için küresel sistemlerin maruziyetini temsil etmek amacıyla pik değeri, pozlama sırasında 2 Watt (W)'da sabitlenmiştir. Taşıyıcı frekansı 900 MHz, modülasyon frekansı 217 Hz, darbe genişliği 577 μsn ve maksimum tepe gücü 2 W olarak ayarlandı.…”
Section: Deneysel Uygulamaunclassified
See 1 more Smart Citation
“…EMA grubuna ait kafeslerin ortasına 20 gün süreyle ve 24 saat boyunca 900 MHz radyo frekansı radyasyonu üreten dijital bir sinyal üreteci olan dijital modülasyon sinyal üreteci (Anritsu MG3670 B tipi, Japonya) cihazının anteni konulmuştur. [21] Dijital modülasyon sinyal üreteci cihaz, mobil iletişim için küresel sistemlerin maruziyetini temsil etmek amacıyla pik değeri, pozlama sırasında 2 Watt (W)'da sabitlenmiştir. Taşıyıcı frekansı 900 MHz, modülasyon frekansı 217 Hz, darbe genişliği 577 μsn ve maksimum tepe gücü 2 W olarak ayarlandı.…”
Section: Deneysel Uygulamaunclassified
“…Taşıyıcı frekansı 900 MHz, modülasyon frekansı 217 Hz, darbe genişliği 577 μsn ve maksimum tepe gücü 2 W olarak ayarlandı. [21] Tüm denekler elektromanyetik alan uygulamasından on gün sonra 50 mg/kg ketamin hidroklorid (Ketalar®, Eczacıbaşı Parke Davis, İstanbul, Türkiye) ve 10 mg/kg intraperitoneal (ip) ksilazin HC1 (Alfazyne®, Alfasan International BV Woerden®, Hollanda) ile indüklenen anestezi altında servikal dislokasyon ile sakrifiye edilerek uyutuldu.…”
Section: Deneysel Uygulamaunclassified
“…It was reported that mobile phone usage has various biological effects on the kidney. At this point; it was proposed by Bedir et al that the electromagnetic waves originating from the mobile phones may exert hazardous effects on the development of kidneys in rats [ 36 ]. Moreover; it was reported by Ulubay et al that EMR can be counted among the stress factors which may cause extensive renal damage [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…reported that an electromagnetic field (EMF) may have side effects in various tissues and cells [2][3][4] . Although some studies have shown tissues with proliferative epithelial cells during and after pregnancy, reproductive cells and tissues of the hematopoietic system seem potentially sensitive to EMF exposure [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%